Meta-analysis of water stress impact on rice quality in China - Shuhui Han; Xianfeng Liu; David Makowski; Philippe Ciais (Agricultural Water Management)
Climate change will lead to an increase in the frequency of droughts and extreme rainfalls, with a potential negative impact on rice production. Many studies have been conducted to assess the impact of water stress on yields, but much less attention was paid to rice quality, leading to a poor understanding of the effect of water stress on rice grain quality traits, especially in China - a major rice producer. Although a number of individual experiments have been carried out on this topic, no quantitative synthesis has yet been produced. Therefore, to quantify the effect of water stress on rice quality in China, we present here the results of a meta-analysis based on 1341 experimental records collected for seven standard rice quality criteria extracted from 37 articles. We employed random effect models to estimate mean effect sizes measuring the extent of the impact of water stress on rice quality and identify the main driving factors. The results showed that water stress significantly increased grain chalky rate by 7.63 % and chalkiness by 17.7 % and significantly decreased the milling quality indexes (brown rice rate decreased by 0.8 %, milled rice rate decreased by 0.9 %, and head rice rate decreased by 2 %) compared to well-watered conditions, both effects leading to reduced rice quality. Water stress also caused a significant increase in protein content by 4.65 %. Soil water potential had a strong effect on the impact of water stress on rice milling quality, while protein content was mainly regulated by the growth stage at which water stress occurred. These results offer compelling evidence of the effect of water stress on rice quality in China, highlighting the significance of developing climate change adaptation strategies to ensure the maintenance of satisfactory rice quality in the future, thereby fostering the production of high-quality rice with high yield.